Psychopathology of Society and Mythology - A.P., Kotsyubinsky; D.A. , Kotsyubinsky (International Journal of Psychosocial Rehabilitation, 2020)
In the article, normal and pathological (socio-psychopathological) forms of mass (collective) consciousness are considered from the point of view of the mental health of society. It is noted that the postinformational (supersaturated with information, a significant part of which is “simulacra”) society plays the role of public distress and deforms social norms and values. This circumstance contributes to the “anomie” (the absence of norms) as a variety of social pathology and as a whole is a complex of challenges addressed to the ability of modern people to successful psychological adaptation. The difficulty of the process of rational assimilation of established ideo-behavioral norms and patterns gives an impetus to the development of irrational phenomena in society—mythological mechanisms of perception of reality and the “social paranoia.". The latter is fraught with two dangerous socio-psychological pathologies that have a psychiatric aspect: 1) general increase in the anxiety that promotes the spread of anxiety and depressive disorders; 2) strengthening of religio-obscurantist tendencies in the public consciousness, which hinder the effective treatment of mentally ill patients. In the article, two sociopsychological phenomena that prevent timely and effective treatment of mentally ill patients are examined: 1) strengthening of the religious obscurantism; 2) mythological fear of psychiatry. It is pointed out that the demonic possession being a source of mental disorders and the exorcism being a method of liberation from these ailments are widespread ideas in society. The author’s classification of the basic psychiatric myths existing in Russian society is offered. It is noted that the immediate goal of reforming society’s views on psychiatry (their demythologization) should be the establishment of a firm and sustainable desire for a mutual cooperation of society, on the one hand, and psychiatrists, on the other.